TDAG8 activation inhibits osteoclastic bone resorption. Issue 2 (12th November 2013) - Hikiji, Hisako; Endo, Daisuke; Horie, Kyoji; Harayama, Takeshi; Akahoshi, Noriyuki; Igarashi, Hidemitsu; Kihara, Yasuyuki; Yanagida, Keisuke; Takeda, Junji; Koji, Takehiko; Shimizu, Takao; Ishii, Satoshi
Abstract : Although the roles of acids in bone metabolism are well characterized, the function of proton‐sensing receptors in bone metabolism remains to be explored. In this study, we evaluated the role of proton‐sensing receptor T‐cell death‐associated gene 8 (TDAG8) in osteoclastic activity during bone loss after ovariectomy. Through observations of bone mineral content, we found that pathological bone resorption was significantly exacerbated in mice homozygous for a gene trap mutation in the Tdag8 gene. Furthermore, osteoclasts from the homozygous mutant mice resorbed calcium in vitro more than the osteoclasts from the heterozygous mice did. Impaired osteoclast formation under acidic conditions was ameliorated in cultures of bone marrow cells by Tdag8 gene mutation. Extracellular acidification changed the cell morphology of osteoclasts via the TDAG8‐Rho signaling pathway. These results suggest that the enhancement of TDAG8 function represents a new strategy for preventing bone resorption diseases, such as osteoporosis.—Hikiji, H., Endo, D., Horie, K., Harayama, T., Akahoshi, N., Igarashi, H., Kihara, Y., Yanagida, K., Takeda, J., Koji, T., Shimizu, T., Satoshi, I. TDAG8 activation inhibits osteoclastic bone resorption. FASEB J. 28, 871–879 (2014). www.fasebj.org